Insights into Aquifer and Borehole Thermal Energy Storage Systems for Slovenia’s Energy Transition - Karlo Borko; Mihael Brenčič; Zdenko Savšek; Jure Knez; Aleš Vozelj; Gregor Kisel; Nina Rman (Energies, 2025)
Since the heating and cooling sectors consume most of the energy in Europe through fossil fuels, the transition to a low-carbon and sustainable energy system is crucial. Underground Thermal Energy Storage (UTES) systems, such as aquifer thermal energy storage (ATES) and borehole thermal energy storage (BTES), offer promising solutions by enabling seasonal storage of renewable thermal energy, balancing the mismatch between supply and demand. ATES and BTES systems store excess heat or cold for later use, making them suitable for large-scale applications like residual heat storage from industrial or power generation processes by offering flexibility in heating and cooling. This review explores the geological and hydrogeological requirements for ATES and BTES systems, pointing out the importance of basic geological knowledge, laboratory and field investigations, and operational monitoring to optimize their performance. The study highlights the need for Slovenia to use the experiences of other European nations to overcome initial challenges, develop effective site evaluation methods, and integrate these systems into existing energy infrastructure.